Radiological surveillance in multiple endocrine neoplasia type 1: a double-edged sword?. Issue 3 (April 2017) - Casey, Ruth Therese; Saunders, Deborah; Challis, Benjamin George; Pitfield, Deborah; Cheow, Heok; Shaw, Ashley; Simpson, Helen Lisa
Abstract : Context: Multiple endocrine neoplasia type 1 (MEN1) is a hereditary condition characterised by the predisposition to hyperplasia/tumours of endocrine glands. MEN1-related disease, moreover, malignancy related to MEN1, is increasingly responsible for death in up to two-thirds of patients. Although patients undergo radiological and biochemical surveillance, current recommendations for radiological monitoring are based on non-prospective data with little consensus or evidence demonstrating improved outcome from this approach. Here, we sought to determine whether cumulative radiation exposure as part of the recommended radiological screening programme posed a distinct risk in a cohort of patients with MEN1. Patients and study design: A retrospective review of 43 patients with MEN1 attending our institution between 2007 and 2015 was performed. Demographic and clinical information including phenotype was obtained for all patients. We also obtained details regarding all radiological procedures performed as part of MEN1 surveillance or disease localisation. An estimated effective radiation dose (ED) for each individual patient was calculated. Results: The mean ED for the total patient cohort was 121 mSv, and the estimated mean lifetime risk of cancer secondary to radiation exposure was 0.49%. Patients with malignant neuroendocrine tumours (NETS) had significantly higher ED levels compared to patients without metastatic disease ( P  < 0.0022). Conclusions: In MEN1, radiological surveillance is associated with clinically significant exposure to ionising radiation. In patients with MEN1, multi-modality imaging strategies designed to minimise this exposure should be considered.